Penerapan Sistem Informasi untuk Meningkatkan Efisiensi Operasional dan Pengambilan Keputusan di Perusahaan - Arujisaputra, Erwin Teguh (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The application of information systems has become a critical factor in enhancing operational efficiency and supporting effective decision-making in modern organizations. This study explores the role of information systems in improving corporate performance through a qualitative approach, utilizing a literature review and library research methods. By synthesizing insights from scholarly articles, case studies, and organizational reports, this research investigates how information systems streamline processes, optimize resource utilization, and facilitate data-driven decision-making. The findings reveal that information systems significantly contribute to automating repetitive tasks, reducing human error, and enhancing collaboration across departments. Additionally, these systems provide real-time analytics and comprehensive reports, enabling managers to make informed strategic decisions swiftly. The study also identifies challenges in information system implementation, including resistance to change, high costs, and the need for continuous training. Addressing these issues through proper planning, stakeholder engagement, and scalability considerations can maximize the benefits of information systems. This research highlights the transformative potential of information systems in corporate environments, providing valuable insights for practitioners and academics aiming to leverage technology for organizational success. Future studies are encouraged to focus on empirical validation and explore sector-specific applications of information systems to further enrich the discourse.